2019
DOI: 10.1097/phh.0000000000000918
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Informatics in Local and State Health Agencies: An Update From the Public Health Workforce Interests and Needs Survey

Abstract: Objective: To characterize public health informatics (PHI) specialists and identify the informatics needs of the public health workforce. Design: Cross-sectional study. Setting: US local and state health agencies. Participants: Employees from state health agencies central office (SHA-COs) and local health departments (LHDs) participating in the 2017 Public Health Workforce Interests and Needs Survey (PH WINS). We characterized and compared the job roles for self-reported PHI, "information technology specialist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…We observed that all 14 HDs in this assessment, regardless of the sophistication of their data collection and informatics systems, faced hurdles. 32 , 33 These challenges included missing and incomplete data, paper-based records, disparate digital databases without common identifiers, and insufficient personnel to maintain, improve, or implement new systems. Most data systems were rapidly designed and were primarily intended to prioritize individual patient care and follow-up, rather than produce summary data describing the HD’s case investigation and contact tracing performance.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that all 14 HDs in this assessment, regardless of the sophistication of their data collection and informatics systems, faced hurdles. 32 , 33 These challenges included missing and incomplete data, paper-based records, disparate digital databases without common identifiers, and insufficient personnel to maintain, improve, or implement new systems. Most data systems were rapidly designed and were primarily intended to prioritize individual patient care and follow-up, rather than produce summary data describing the HD’s case investigation and contact tracing performance.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that these findings are indications of a favorable assessment of the cost-benefit ratio of implementation of technology-based systems relative to low-cost health data systems. Adequate staffing and funding for state health data systems is lacking, which has impeded or slowed progress or halted data dissemination efforts in these states [ 25 , 26 ]. Our findings are more important than ever, given the reliance of society on trusted, reliable, and accurate public health data [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Public health informatics has long been recognized as a critical need in state and local health agencies; however, recent research estimates that informatics positions account for only 1% of state health agency workforces. 3 Although historically the distinction between the role of informatics and information technologists has not been well understood, national efforts to clearly define the roles and skills of informatics professionals have provided a clearer picture of how these two branches of information science are distinct yet complementary. 3 , 4 Informatics is categorized as a core science of public health where informaticians serve as the knowledge architects of public health information systems.…”
Section: A Public Health Informatics Foundationmentioning
confidence: 99%
“… 3 Although historically the distinction between the role of informatics and information technologists has not been well understood, national efforts to clearly define the roles and skills of informatics professionals have provided a clearer picture of how these two branches of information science are distinct yet complementary. 3 , 4 Informatics is categorized as a core science of public health where informaticians serve as the knowledge architects of public health information systems. 4 Informaticians use their knowledge of data security, standards, and policy to translate public health program system needs into functional requirements for public health information and surveillance systems.…”
Section: A Public Health Informatics Foundationmentioning
confidence: 99%